Tumor necrosis factor alpha and interleukin 1 stimulate the human immunodeficiency virus enhancer by activation of the nuclear factor kappa B. - Osborn, L (1989)
Binding of peptide hormones to surface membrane receptors leads to the transcription of specific genes within relevant target cells. How these signals are transduced to alter gene expression is largely unknown, but this mechanism probably involves a sequence of enzymatic steps that activate factors in the nucleus that modulate transcription. We now demonstrate that two different peptide hormones, or cytokines, stimulate the human immunodeficiency virus enhancer, and this effect is mediated by nuclear factor (NF) kappa B (nuclear factor that binds the kappa immunoglobulin light chain gene enhancer). These cytokines, tumor necrosis factor alpha and interleukin 1, act on multiple cell types and represent the only naturally occurring activators of this transcription factor among eight cytokines examined. Although NF-kappa B binding can be stimulated by phorbol 12-myristate 13-acetate, tumor necrosis factor alpha acts through an independent mechanism, inducing NF-kappa B binding in HT-2 cells, which did not show increased binding in response to phorbol 12-myristate 13-acetate, and causing superinduction in Jurkat T-lymphoma cells. Tumor necrosis factor alpha is also a more selective activator of T cells than phorbol 12-myristate 13-acetate, having no effect on lymphokine production in EL-4 cells at the same time it induces NF-kappa B. These findings suggest that human immunodeficiency virus gene expression can be induced in T cells without activating lymphokine secretion and that the role of these cytokines in the activation of latent human immunodeficiency virus infection deserves further clinical evaluation. Finally, this link between binding at the surface membrane and stimulation of a specific transcription factor should help define intermediates for these cytokine activation pathways.